Гекзаметр та його деривати в румунській поезії кінця ХІХ — початку ХХ століття - Paladian, Kristiniia (Видавництво ХНУ імені В.Н.Каразіна, 2014)
The article discusses the first attempts of imitation of hexameter in original Romanian literature from the end of 19th century till the beginning of 20th century. It is proved that in Romanian poetry hexameter is expressed as an imitation of three forms of antique size: the equivalent or the right antique form of Greek sample with the reproduction of primary type of rhythm; dactylic-trochaic variations of Latin sample with one top rhythm and dactylic-trochaic variations of German sample with two tops rhythm; derivatives of hexameter.
Hexameter and its derivatives in Romanian poetry from the end of 19th century till the bеginning of 20th century
Keywords: versification; hexameter; derivate of hexameter; meter; rhythm; caesura